2011
DOI: 10.1158/2159-8274.cd-10-0020
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Two-Stage, Transdisciplinary Study Identifies Digoxin as a Possible Drug for Prostate Cancer Treatment

Abstract: Identification of novel indications for commonly prescribed drugs could accelerate translation of therapies. We investigated whether any clinically-used drugs might have utility for treating prostate cancer by coupling an efficient, high-throughput laboratory-based screen and a large, prospective cohort study. In stage 1, we conducted an in vitro prostate cancer cell cytotoxicity screen of 3,187 compounds. Digoxin emerged as the leading candidate given its potency in inhibiting proliferation in vitro (mean IC5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
160
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(165 citation statements)
references
References 23 publications
3
160
2
Order By: Relevance
“…In drug screening, digoxin was found to be among the most potent of commonly used drugs in inhibiting growth of prostate cancer cell lines (25). In the same study, the investigators examined risk in men using digoxin, finding a lower prostate cancer incidence (0.76; 95% CI, 0.61-0.95), compared with nonusers of digoxin (25). Further studies are needed to confirm this result, but the result is consistent with digoxin exerting an estrogenic effect.…”
Section: Digitalis and Cancer Riskmentioning
confidence: 99%
“…In drug screening, digoxin was found to be among the most potent of commonly used drugs in inhibiting growth of prostate cancer cell lines (25). In the same study, the investigators examined risk in men using digoxin, finding a lower prostate cancer incidence (0.76; 95% CI, 0.61-0.95), compared with nonusers of digoxin (25). Further studies are needed to confirm this result, but the result is consistent with digoxin exerting an estrogenic effect.…”
Section: Digitalis and Cancer Riskmentioning
confidence: 99%
“…Importantly and most excitingly, bufalin sensitizes breast and lung cancer cells to the inhibitory effects of other chemotherapeutics and inhibits primary tumor growth in vivo. Other groups also reported that bufalin and other cardiac glycosides can inhibit transcription factors and induce synergistic immune responses (19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Unfortunately, cardiac glycosides are well known for their cardiotoxicity.…”
mentioning
confidence: 99%
“…As with any observational study, biases could partially account for these findings. Digoxin users were more likely to be white, less likely to have a family history of prostate cancer, and more likely to use cholesterollowering drugs and aspirin regularly, all factors that could contribute to the findings reported by Platz and colleagues (4). In addition, digoxin users tended to be older (and therefore may have surpassed the peak age of receiving a diagnosis of prostate cancer) or, because of their cardiac problems, may not have lived long enough to develop prostate cancer, circumstances also possibly contributing to a reduced risk of prostate cancer in digoxin users.…”
Section: In the Spotlightmentioning
confidence: 82%